PENGEMBANGAN LEMBAR KERJA SISWA BERORIENTASI DISCOVERY LEARNING PADA PEMBELAJARAN MATEMATIKA DI KELAS IV SEKOLAH DASAR - Ridania Ekawati (Menara Ilmu, 2018)
Student worksheet (LKS) is one of the learning tools that can enable students inlearning. LKS mathematics are widely used basically not in accordance with thecharacteristics of students and yet accommodate the students to develop their creativethinking skills to solve problems. Such circumstances become one of the triggers of lowactivity of the students than teachers in learning. This fact necessary to find a solution inthe form of developing LKS. This solution is realized in the form of developing LKSDiscovery Learning valid oriented, practical, and effective. This type of research is thedevelopment of research. This study adopts a model McKenny, consisting of thepreliminary analysis phase, design phase, and assessment phase. LKS developed validatedby linguists, content and construct. Kepratisan seen through the observation of learningimplementation, the questionnaire responses of students and teachers. Effectiveness seenthrough observation of activities and results of students' creative thinking in finding theconcept of learning. The results showed that the Discover LKS oriented Learning to fourthgrade have developed valid criteria in terms of content, approach, format, and language.Validity of LKS developed in the category valid. Observation, questionnaires, andinterviews indicate that the LKS has been practical in terms of ease of use, time of use, andreadability by teachers and students. In addition, LKS developed has also been effective inincreasing student activity in learning and can develop creative thinking abilities ofstudents through the novelty of the concept, flexibility and fluency. Based on these results,we can conclude that the LKS berorientasiDiscovery Learningyang developed for fourthgrade students declared valid, practical, and effective.Keywords : Mathematics, Discovery Learning, LKS